Modeling the Suspended Sediment Transport in a Very Wide, Shallow, and Microtidal Estuary, the Río de la Plata, Argentina - Moreira, Diego (2019)
The impact of the diverse processes responsible for the distribution of suspended sediments in the wide, shallow, and microtidal Río de la Plata estuary and the adjacent shelf is studied by means of a set of process-oriented numerical simulations. Model results show that the large width and the geometry of the estuary play a major role in the sedimentation processes. The widening and deepening of the estuary drives a significant reduction in current speeds at (i) the confluence of the tributaries and (ii) downstream Barra del Indio Shoal. Thus, sediment deposition enhances downstream those areas. Even though tides are of small amplitude in the study area, they have a significant impact on lateral mixing and resuspension of the bottom sediments. Resuspension augments the concentration of fine sediments in the layers close to the bottom, but tidal energy is not enough to lift them to the surface. Winds (which can be quite strong over this area) enhance horizontal mixing, smoothing the pattern produced by tides. Wind waves increase the concentration of sediment by vertical mixing, and their effect is most evident along the southern coast where wind waves lift the sediments resuspended by tides to the surface. The estuarine circulations associated to the bottom salinity front acts retaining sediments upstream the Barra del Indio Shoal, where estuarine currents and flocculation play an important role in sediment deposition.